2019
DOI: 10.1063/1.5087865
|View full text |Cite
|
Sign up to set email alerts
|

Predissociation dynamics of D2 + hv → D(1s1/2) + D(2p1/2,3/2, 2s1/2) revealed by the spin-orbit state resolved fragment branching ratios and angular distributions

Abstract: For molecular photodissociations, the spin-orbit state resolved fragment branching ratios and angular distributions provide deep insight into the dynamics. For the first excited state of the H(2p1/2,3/2) atom, a branching ratio measurement is a challenge because of small energy spacing between them. For the D(2p1/2,3/2) fragments from the predissociation of D2 + 14.76 eV → D(1s) + D(2s, 2p1/2,3/2) in the 2pπC1Πu (υ = 19) state, we made such measurements by pumping the D(2s, 2p1/2,3/2) fragments to high-lying R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Moreover, it is possible to polarize the reactants bond-axis or rotational angular momentum, so it can be achieved some control into the relative geometry of the reactants before their interactions. For the non-familiar reader that may sound utopia, but several groups have succeeded in carrying out such experiments using either optical alignment methods, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] brute force through intense laser fields [17][18][19][20][21][22][23][24][25][26][27][28], or using static orienting fields in tandem with hexapole state selection. [29][30][31][32][33][34][35] Based on the experimental set-up by Kandel et al, [11] in a series of articles we have suggested a hypothetic crossed-beam experiment for atom-diatom reactions where the diatom (in this case D 2 ) is prepared in a |v = 0, j = 2, m = 0 state, where v, j, and m are the vibrational, rotational and magnetic quantum number.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is possible to polarize the reactants bond-axis or rotational angular momentum, so it can be achieved some control into the relative geometry of the reactants before their interactions. For the non-familiar reader that may sound utopia, but several groups have succeeded in carrying out such experiments using either optical alignment methods, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] brute force through intense laser fields [17][18][19][20][21][22][23][24][25][26][27][28], or using static orienting fields in tandem with hexapole state selection. [29][30][31][32][33][34][35] Based on the experimental set-up by Kandel et al, [11] in a series of articles we have suggested a hypothetic crossed-beam experiment for atom-diatom reactions where the diatom (in this case D 2 ) is prepared in a |v = 0, j = 2, m = 0 state, where v, j, and m are the vibrational, rotational and magnetic quantum number.…”
Section: Introductionmentioning
confidence: 99%